Content of autoantibodies in teenagers with chronic pathology of upper respiratory tract who live in an industrial center - L. B. Masnavieva (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Conditions of environment can become causes of developments of different pathologic processes in people, living in ecologically unfavorable regions. The aim. of the work was to study contents of autoantibodies in blood serum of teenagers with chronic pathology of respiratory tract living in areas contaminated with emissions of petrochemical industry. We examined teenagers living near petrochemical industry and. in commuter towns. In each area people with and. without chronic pathology of respiratory tract were marked out. We studied the levels of serum autoantibodies to antigens that characterize condition of immune system. (nDNA, β2-glycoprotein I, Fc-enzyme, IgG). The changes of autoantibodies contents can tell about peculiarities of course of adaptive processes in teenagers living in the conditions of technogenic load.